The Relationship of Depression, Anxiety and Stress with Childbirth Self-Efficacy in Nulliparous Pregnant Women : Childbirth Self-efficacy, Depression, Anxiety and Stress - Baanei Heravan, Mahsima; Rashki, Sadaf (Advances in Nursing & Midwifery, 2021)
Introduction: Childbirth is one of the divine gifts for the production of the human race on earth; but one of the important factors involved in avoiding vaginal childbirth is the childbirth self-efficacy. On the other hand, many changes occur during pregnancy that lead to increased depression, anxiety, and distress. Whereas self-efficacy affects all aspects of behavior and emotional activities such as anxiety, stress, and thought patterns; therefore, this study was aimed to determine the relationship of depression, anxiety, and stress with childbirth self-efficacy in nulliparous pregnant women. Methods: This study is a descriptive- predictor correlation study that it is done over 323 nulliparous pregnant women referring to health centers in Zahedan city in 2020-2021. Data were collected using Individual questionnaire, Lowe childbirth self-efficacy questionnaire and DASS21 scale. The data was analyzed using Spearman correlation coefficients test, Liner regressions model and Multiple regression in SPSS version 22. A statistical significance was deemed present when the P-value was less than0.05. Results: Results of Spearman correlation coefficients test didn’t show a significant direct correlation between childbirth self-efficacy with depression, anxiety and stress (p>0.05). According to Liner regressions model, none of the variables of depression, anxiety and stress had a significant level of less than 0.05 and isn’t considered as a predictor variable of childbirth self-efficacy(p>0.05). Conclusion: Since there is no significant relationship between depression, anxiety and stress with childbirth self-efficacy in nulliparous pregnant women, it is suggested that more studies be conducted in this field with more samples and in other societies.